Public-Private Investment Partnerships: Efficiency Estimation Methods - Trynov, Aleksandr Valeryevich (Economy of Regions, 2016)
The article focuses on assessing the effectiveness of investment projects implemented on the principles of public-private partnership (PPP). This article puts forward the hypothesis that the inclusion of multiplicative economic effects will increase the attractiveness of public-private partnership projects, which in turn will contribute to the more efficient use of budgetary resources. The author proposed a methodological approach and methods of evaluating the economic efficiency of PPP projects. The authors technique is based upon the synthesis of approaches to evaluation of the project implemented in the private and public sector and in contrast to the existing methods allows taking into account the indirect (multiplicative) effect arising during the implementation of project. In the article, to estimate the multiplier effect, the model of regional economy - social accounting matrix (SAM) was developed. The matrix is based on the data of the Sverdlovsk region for 2013. In the article, the genesis of the balance models of economic systems is presented. The evolution of balance models in the Russian (Soviet) and foreign sources from their emergence up to now are observed. It is shown that SAM is widely used in the world for a wide range of applications, primarily to assess the impact on the regional economy of various exogenous factors. In order to clarify the estimates of multiplicative effects, the disaggregation of the account of the “industry” of the matrix of social accounts was carried out in accordance with the All-Russian Classifier of Types of Economic Activities (OKVED). This step allows to consider the particular characteristics of the industry of the estimated investment project. The method was tested on the example of evaluating the effectiveness of the construction of a toll road in the Sverdlovsk region. It is proved that due to the multiplier effect, the more capital-intensive version of the project may be more beneficial in terms of future tax revenue. The proposed method can be used by the state and municipal authorities in the evaluation and substantiation of projects on a public-private partnership.